2009
DOI: 10.1016/j.pupt.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Bronchodilator effects of indacaterol and formoterol in patients with COPD

Abstract: Background Resting inspiratory capacity (IC) reflects static hyperinflation in chronic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 18 publications
4
26
0
3
Order By: Relevance
“…This improvement in dyspnoea (TDI) was accompanied by an improvement of 182 mL in resting IC after 14 days of treatment with indacaterol compared with placebo, together with significant improvement (p < 0.05) in trough FEV 1 of 145 mL. These results are consistent with a previous study that showed that a single dose of indacaterol demonstrated greater improvements in both resting IC and FEV 1 compared with twice daily formoterol(5), and confirm the 24-h bronchodilator efficacy of indacaterol in patients with COPD. Likewise, in the indacaterol treatment groups, there were improvements in a range of volume measures including FVC, VC and RV.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This improvement in dyspnoea (TDI) was accompanied by an improvement of 182 mL in resting IC after 14 days of treatment with indacaterol compared with placebo, together with significant improvement (p < 0.05) in trough FEV 1 of 145 mL. These results are consistent with a previous study that showed that a single dose of indacaterol demonstrated greater improvements in both resting IC and FEV 1 compared with twice daily formoterol(5), and confirm the 24-h bronchodilator efficacy of indacaterol in patients with COPD. Likewise, in the indacaterol treatment groups, there were improvements in a range of volume measures including FVC, VC and RV.…”
supporting
confidence: 90%
“…In previous studies, indacaterol has demonstrated 24-h bronchodilation (3)(4), with no loss in efficacy on once daily dosing for up to a year (4), and a good overall safety profile (4). Further, in a previous study, a single 300 µg dose of indacaterol had a greater effect on resting IC than formoterol 12 µg administered twice daily (5). The aim of the present study was to evaluate the effect of indacaterol on dynamic and static lung hyperinflation, breathlessness, and health status in patients with moderate-to-severe COPD.…”
Section: Chronic Obstructive Pulmonary Disease (Copd) Is a Chronic Prmentioning
confidence: 79%
“…Five randomised studies were performed in COPD patients Aerolizer ® inhaler) [37]. Indacaterol had a greater effect on peak inspiratory capacity (p ¼ 0.034); cough occurred more frequently following indacaterol administered using the Breezhaler ® device.…”
Section: Nexthaler ® Vs Pmdimentioning
confidence: 99%
“…13 Beier et al também demonstrou que, embora ambos apresentassem efeitos similares sobre o VEF 1 , o indacaterol foi superior ao obter aumento significativo na capacidade inspiratória (CI) comparada à dose recomendada de formoterol. 14 Estudos comparando a eficácia broncodilatadora do indacaterol com o tiotrópio demonstraram superioridade em relação à monoterapia. O estudo de Mahler et al identificou que a associação de tiotrópio e indacaterol promovia aumento da CI e melhor broncodilatação em relação à monoterapia com tiotrópio.…”
Section: Introductionunclassified